A Bio-Psycho-Social Co-created Intervention for Young Adults With Multiple Sclerosis (ESPRIMO): Rationale and Study Protocol for a Feasibility Study - Donisi, Valeria; Gajofatto, Alberto; Mazzi, Maria Angela; Gobbin, Francesca; Busch, Isolde Martina; Ghellere, Annamaria; Klonova, Alina; Rudi, Doriana; Vitali, Francesca; Schena, Federico; Del Piccolo, Lidia; Rimondini, Michela (Frontiers in Psychology, 2021)
Background: Multiple sclerosis (MS), the most common neurological disease that causes disability in youth, does not only affect physical functions but it is also associated with cognitive impairment, fatigue, depression, and anxiety and can significantly impact health related quality of life (HRQoL). Since MS is generally diagnosed at a young age – a period of great significance for personal, relational and professional development – adaptation can become highly challenging. Therefore, enhancing the competences of young people to adaptively cope with these potential challenges is of utmost importance in order to promote their potentialities and talents. It has been shown that psychological interventions targeting MS patients can enhance resilience and HRQoL and that regular physical activity (PA) and social engagement can improve psychological well-being. However, literature on the development of global interventions based on the bio-psycho-social model of disease is missing. Even less attention has been paid to interventions dedicated to young adults with MS (YawMS) and to the involvement of patients in the development of such programs. Aims: In collaboration with MS patients, this study aims to develop a bio-psycho-social intervention (ESPRIMO) for YawMS, aiming to improve their HRQoL and to explore its feasibility, acceptability, and effects. Methods: To tailor the intervention to the specific needs of YawMS, “patient-engagement principles” will be adopted in the co-creation phase, performing a web-survey and focus groups with patients and healthcare professionals. In the intervention phase, a pilot sample of 60 young adults with MS will be enrolled. The co-created intervention, composed of group sessions over a 12-week period, will cover psycho-social strategies and include physical activities. Adopting a longitudinal, pre-post evaluation design, self-report questionnaires measuring HRQoL and other bio-psycho-social features (e.g., resilience, well-being, mindfulness traits, self-efficacy, perceived social support, psychological symptoms, illness perception, committed action, fatigue, attitudes, subjective norms, perceived behavioral control, motivation, perception of autonomy support for PA, barriers and intentions to PA) will be administered, quantity and quality of PA measured and a questionnaire developed by the authors used to evaluate the feasibility and acceptability of the ESPRIMO intervention.